P350 Real-world data regarding treatment of ulcerative colitis patients with golimumab in Switzerland. (25th January 2019) - Perrig, K; Rossel, J-B; Biedermann, L; Schreiner, P; Roth, R; Zeitz, J; Greuter, T; Vavricka, S; Krupka, N; Juillerat, P; Rogler, G; Misselwitz, B
Abstract: Background: Tumour necrosis factor (TNF)-inhibitors have markedly improved treatment of ulcerative colitis (UC), but loss of response in the long-term remains a frequent problem. A novel anti-TNF agent, golimumab, has been introduced in Switzerland for UC in 2014. Methods: We aimed for real-word data from 1536 UC patients from the Swiss IBD cohort study (SIBDC). UC patients treated with golimumab from 2014 to 2018 were compared with the remaining SIBDC patients with UC. We also performed a chart review of a subgroup of patients to assess response to golimumab. Results: Among 90 patients (5.9% of all SIBDCS patients with UC) treated with golimumab, extensive disease (E3) was more frequent compared with the non-golimumab group ( n = 1409); (E3: 61% vs. 54%, E2: 37% vs. 33% and E1: 2% vs. 12%, p = 0.005). They had more active disease (average modified Truelove and Witts activity index [MTWAI] 8 [IQR: 4–10] vs. 4 [IQR: 2–8], p < 0.001) and more extraintestinal manifestations (56/90 [62%] vs. 615/1446 [43%], p < 0.001). In the golimumab group, previous treatment with infliximab, adalimumab, certolizumab or vedolizumab was common (26 patients [~29%] with 0 biologics, 44 patients [~49%] with 1, 17 [~19%] with 2, 3 [3%] with 3 biologics) and the rate of prior anti-TNF failure was higher than in the non-golimumab group ( p ≤ 0.001 for each biologic). Chart review for 57 patients showed a drop of MTWAI from 7 (IQR: 4–11) at baseline to 3 (IQR: 2–6.5) at 6 months ( p = 0.0006) and to 2 (IQR: 1–5) at 12 months ( p < 0.0001) upon golimumab therapy (Figure). Similarly, the partial Mayo score decreased from 3 (IQR: 1.75–5.25) to 0.5 (IQR: 0–4, p = 0.0002) and 1 (IQR: 0–3.5, p = 0.001) at 6 and 12 months, respectively. The partial Mayo score was normal for 17/35 patients (30% of original cohort) at 6 months and for 14/28 patients (25% of original cohort) at 12 months, respectively. Golimumab was continued in 23/57 patients beyond 12 months. The most frequent reason for stopping was golimumab failure (21 patients). Conclusions: Golimumab has been used in Switzerland mainly for UC patients with severe and extensive disease and failure of prior biologic therapy. A quarter of this difficult to treat (70% with ≥ 1 biological treatment failure) patient population could be successfully treated with normalisation of the partial Mayo score at 12 months.